Energy Consumption and Manufacturing Performance in Sub-Saharan Africa: Does Income Group Matters? - Hassan, Sallahuddin; Danmaraya, Ismail Aliyu; Danlami, Muhammad Rabiu (International Journal of Energy Economics and Policy, 2018)
This paper investigates the link connecting energy consumption with manufacturing performance using panel data for sampled low-income Sub-Saharan Africa (SSA) and middle-income SSA during the period 1995-2013. The panel cointegration test provides evidence of cointegration among the variables for both the low-income and the middle-income group in SSA. The result of the Fully Modified Ordinary Least Square indicates that in the long run, increase in energy consumption leads to increase in manufacturing performance for both the sampled low-income and middle-income SSA countries. This implied that both the low-income and middle-income SSA countries are energy dependent countries. In this regard, this study shows that energy is a relevant factor in socio-economic development for both the low-income and the middle-income SSA countries. Thus, policies on energy that will ensure lower negative impact on manufacturing performance are recommended. Keywords: Energy Consumption, Manufacturing Performance, Sub-Sahara Africa. JEL Classifications: Q430, Q470